They are not destined to fail: a systematic examination of scores on embedded performance validity indicators in patients with intellectual disability - Messa, Isabelle; Holcomb, Matthew; Lichtenstein, Jonathan D; Tyson, Brad T; Roth, Robert M; Erdodi, Laszlo A (Australian journal of forensic sciences, 2022)
This study was designed to determine the clinical utility of embedded performance validity indicators (EVIs) in adults with intellectual disability (ID) during neuropsychological assessment. Based on previous research, unacceptably high (>16%) base rates of failure (BR Fail ) were predicted on EVIs using on the method of threshold, but not on EVIs based on alternative detection methods. A comprehensive battery of neuropsychological tests was administered to 23 adults with ID (M Age = 37.7 years, M FSIQ = 64.9). BR Fail were computed at two levels of cut-offs for 32 EVIs. Patients produced very high BR Fail on 22 EVIs (18.2%-100%), indicating unacceptable levels of false positive errors. However, on the remaining ten EVIs BR Fail was <16%. Moreover, six of the EVIs had a zero BR Fail , indicating perfect specificity. Consistent with previous research, individuals with ID failed the majority of EVIs at high BR Fail . However, they produced BR Fail similar to cognitively higher functioning patients on select EVIs based on recognition memory and unusual patterns of performance, suggesting that the high BR Fail reported in the literature may reflect instrumentation artefacts. The implications of these findings for clinical and forensic assessment are discussed.